Gestational Anemia (Garbhini Pandu) - A Critical Analysis (AYUSHDHARA, 2022)
Pregnancy is a unique joyful experience in every woman’s life. It is associated with many complications, where Anaemia is one among them. Woman indeed is the source of human progeny. When protected, she protects the progeny. Pregnancy is the milestone event of a woman’s life which transforms her from woman to a mother. Though it is a joyful journey, it is associated with lots of physical and physiological alterations which give rise to some health issues. Gestational anaemia is one of common health issue occurring in pregnancy on large scale in developing countries that requires an immediate intervention to save the life of both the mother the child. Ayurveda, an ancient Indian science has given more importance to the women and her health with vast descriptions of pregnancy, labour and its complications with management. Ayurveda has recorded some of the complications of pregnancy under the name Garbhopdravas. Garbhini Pandu is the commonest Upadrava among them. Garbhini Pandu is described as a symptom and not as a Vyadhi in Ayurveda classics. The present study evaluates in detail about the Garbhini Pandu and its management that is elucidated in Ayurveda and the study also attempted to explicate the correlational features with the Modern science.